"The universities". I - University College, Dublin - Meenan, James (Statistical and Social Inquiry Society of Ireland, 1946)
University education has ceased to excite more than passing interest since the Irish Universities Act of 1908. The University of Dublin, indeed, has been examined by a Royal Commission since that date; but there has been no inquiry into the developments in University education as a whole or into the degree to which the arrangements made in 1908 have justified the hopes reposed in them. The present paper, it is hoped, will be the first of a series in which the progress of the five University institutions will be examined.
Read Thursday, May 31st, 1945
Keywords: University College Dublin; Education in Ireland; Irish universities; 314.15